THE INFLUENCE OF LEARNING MOTIVATION AND POSITIVE CULTURE ON THE LEARNING OUTCOMES OF WRITING POPULAR ARTICLES OF HIGH SCHOOL STUDENTS IN THE PANDEGLANG REGENCY - Romdiah, Yayah; Dja'far, Harmi Ibnu (Journal of Language and Literature Education, 2024)
ABSTRACT In principle, teaching should focus on self-development, developing the child's morals, body and soul so that students are formed as individuals who are independent and have character. This is in line with the various government programs that have recently been rolled out, including education and training, seminars, workshops which must be attended by teachers as educators so that students' cognitive, affective and psychomotor abilities increase. However, the phenomena occurring in the field are inversely proportional to what the government has programmed. The facts show that students still find difficulties in learning, especially in writing popular articles, so this can make it difficult for students to obtain satisfactory learning results, so it is deemed necessary to have motivation and a positive culture in learning. Therefore, this research aims to determine the influence of learning motivation and positive culture on students' learning outcomes in writing popular articles using quantitative research methods. The research results show that there is a variable that has the most influence on students' learning outcomes to write popular articles, namely positive culture.